Penyuluhan Inkontenesia Urin pada Lansia di UPTD Dinas Pelayanan Sosial Binjai Sumatera Utara Tahun 2024 - Tahan Tahan; Indra Agussamad; Erika Erika; Sri Muliati; Eko Murdianto; Daniel Chanda Situmeang; Elfrida Lamtama Situmorang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Urinary incontinence occurs when a person's urine leaks unknowingly or unintentionally. Urinary incontinence varies in the form of urine excretion which is sometimes only a few drops or vice versa it is really a lot. One way to prevent urinary incontinence is to treat it, and doing Kegel exercises is one way to deal with it. (Sangga, M.W, R.C Choeron & Y Rosdiana, 2021). This community service activity aims to increase the knowledge of the elderly about urinary incontinence and how to overcome the problem of urinary incontinence. This community service activity uses the lecture method, and questions and answers and kegel gymnastics exercises. The lecture method was carried out by delivering material about urinary incontinence, the question and answer method was carried out by asking participants about the material that had been presented and doing kegel exercises in the elderly. The results of this community service activity were obtained that participants were able to understand and apply the material that had been delivered and perform kegel exercises independently. Based on the community service activities that have been carried out, the elderly are enthusiastic about accepting the entire series of activities ranging from the percentage of material delivery to the implementation of service running with Lanca, the elderly are very active in asking and answering questions and actively participating in kegel gymnastics training.